Patterns of marriage and reproductive practices: is there any relationship?. (2nd January 2017) - Vedadhir, Abouali; Taghizadeh, Ziba; Behmanesh, Fereshteh; Ebadi, Abbas; Pourreza, Abulghasem; Abbasi-Shavazi, Mohammad Jalal
Abstract: Today, a transition from traditional to modern marriages can be observed in many countries. This shift in patterns of marriage has evidently affected childbearing and reproductive practices. This study aimed to examine the relationship between patterns of marriage and reproductive practices in Iran. Hence, 880 married women, aged 15–49 years old, living in the North of Iran were selected using a multi-stage cluster sampling strategy and their patterns of marriage and reproductive practices were cross sectionally studied. The results revealed that there were no significant differences in the reproductive practices by three main patterns of marriage in Babol, Iran. The study also indicated that there were no significant differences in reproductive practices in three patterns of marriage after controlling for socio-economic variables. It seems that apart from the patterns of marriage, other influencing factors are the determinants of fertility in women, and the policy-makers of Iran need to pay attention to these determinants before making any decisions in this area.